The three main monotheistic religions and gm food technology: an overview of perspectives - Singer Peter A; Omobowale Emmanuel B; Daar Abdallah S (BMC, 2009)
Abstract Background Public acceptance of genetically modified crops is partly rooted in religious views. However, the views of different religions and their potential influence on consumers' decisions have not been systematically examined and summarized in a brief overview. We review the positions of the Judaism, Islam and Christianity - the three major monotheistic religions to which more than 55% of humanity adheres to - on the controversies aroused by GM technology. Discussion The article establishes that there is no overarching consensus within the three religions. Overall, however, it appears that mainstream theology in all three religions increasingly tends towards acceptance of GM technology per se, on performing GM research, and on consumption of GM foods. These more liberal approaches, however, are predicated on there being rigorous scientific, ethical and regulatory scrutiny of research and development of such products, and that these products are properly labeled. Summary We conclude that there are several other interests competing with the influence exerted on consumers by religion. These include the media, environmental activists, scientists and the food industry, all of which function as sources of information and shapers of perception for consumers.